An evidence-driven approach to scrum law modifications in amateur rugby played in South Africa. Issue 14 (18th February 2014) - Hendricks, Sharief; Lambert, Mike I; Brown, James C; Readhead, Clint; Viljoen, Wayne
Abstract : Background: In 2012, the South African Rugby Union (SARU) approved a new set of scrum laws for amateur rugby played in the country, to be implemented at the start of the 2013 rugby season. These law changes were primarily based on the relatively high proportion of scrum-related catastrophic injury data collected as part of the BokSmart National Rugby Safety Programme ( BokSmart ) over the preceding 4 years (2008–2011). Aim: To describe the scrum-related catastrophic injury data in South Africa over the past 5 years (2008–2012), and to discuss how this evidence justifies the change in the Amateur Scrum Laws to make this aspect of the game safer in South Africa. Methods: Catastrophic injury data were collected through BokSmart at amateur and professional levels, during training and matches over 5 years (2008–2012). Results: The scrum phase accounted for 33% (n=20 of 60) of all catastrophic injuries between 2008 and 2012. Eighteen of the 20 scrum injuries (90%) were confirmed as acute spinal cord injuries, with 13 of these being permanent injuries. For the scrum injury mechanisms that were provided (n=19), 'impact on the engagement' was the most frequently reported (n=11 of 19, 58%), followed by 'collapsed scrum' (n=7 of 19, 37%) and 'popping out' (n=1 of 19, 5%). Conclusions: Based on these scrum-related catastrophic injury data, a change in the Amateur Scrum Laws of South African Rugby was justified. The main purpose of these scrum law changes is to reduce the number of scrum-related catastrophic injuries in the country, by minimising the opportunity for impact injury and subsequent scrum collapse in amateur rugby in South Africa, thereby making this aspect of the game of rugby safer.